The Effect of Sustainability Report on Company Value with Corporate Governance as a Moderating Variable - Ryan Hanafuri; Gunarsih, Tri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the effect of sustainability reports on firm value with Corporate Governance as a moderating variable. The population in this study are all companies listed on the Indonesia Stock Exchange (IDX), with a CGPI score from 2014-2021, and companies that publish sustainability reports from 2014-2021. This study used purposive sampling with a sample of 64 observations. The Moderating Regression Analysis (MRA) was applied to test the hypotheses. The results of this study indicate that the sustainability report has a significant positive effect on firm value (H1). Corporate Governance positively and significantly affects firm value (H2). Corporate Governance weakens the relationship between sustainability reports and firm value (H3).